STUDI EKSPLORATIF MANAJEMEN PEMBELAJARAN FIQIH SELAMA COVID-19 DI MTs NEGERI 1 PASAMAN - Sandra, Elvia (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
Learning in the covid-19 period demands innovation from a teacher, this is due to the implementation of learning from home by utilizing various devices. This study aims to find out and analyze the learning management of fiqh subjects during the pandemic. From the results of this study can be presented as follows: first, Fiqh learning planning during the pandemic in MTs Negeri I Pasaman consists of formulating goals, setting teaching materials, determining the source of teaching materials, determining learning methods, and planning assessment of learning outcomes. Second, The implementation of fiqh learning during the pandemic in MTs Negeri I Pasaman by conducting online learning using whatapp group, teaching materials are sent through WA, while practical materials are taught directly by dividing students in accordance with the rules of health protokl. Third, Evaluation of fiqh learning during the pandemic in MTs Negeri I Pasaman also through online, teachers send questions and students send answers via WhatsApp, while practical exams students send self-recorded videos from home. Fourth, the obstacles faced in the implementation of fiqh learning during the pandemic in MTs Negeri I Pasaman not all students' residences have internet networks.